A tutela da privacidade de dados na era do Big Data - Russo, Rogério Agueda (2020)
This paper analyzes the protection of citizens’ privacy in the modern economy, based on the use of information from structured databases into business, in the most varied segments. As the Data Protection Act will be effective soon in Brazil, which guarantees new rights regarding personal data, new obligations and duties for data-processing agents will arise, emerging the necessity to comply with such rules. Considering data is deemed as the “new oil”, the compliance with legislation by the companies is essential for the sustainable use of technologies into business processes, as well for guarantying protection of citizens’ fundamental rights based on privacy. It will be presented the legal concepts related to the protection of personal data, as well as the innovations introduced by the new Brazilian rules, comparing with the European recent experience, as well as the businesses’ compliance journey observing the data protection